The Effect of Exogenous Ketone Monoester Ingestion on Plasma BDNF During an Oral Glucose Tolerance Test - Walsh, Jeremy J.; Myette-Côté, Étienne; Little, Jonathan P. (Frontiers in Physiology, 2020)
Brain-derived neurotrophic factor (BDNF) is important for brain and metabolic function. Ingestion of a ketone monoester (KME) drink containing beta-hydroxybutyrate (β-OHB) attenuates hyperglycemia in humans and increases neuronal BDNF in rodents. Whether KME affects BDNF in humans is currently unknown. This study examined the effect of KME ingestion before an oral glucose tolerance test (OGTT) on plasma BDNF in normal-weight adults (NW) and adults with obesity (OB). Methods: Exploratory, secondary analyses of two studies were performed. Study 1 included NW (n = 18; age = 25.3 ± 4.3 years; BMI = 22.2 ± 2.3 kg/m2) and Study 2 included OB (n = 12; age = 48.8 ± 9.5 years; BMI = 33.7 ± 5.0 kg/m2). Participants ingested 0.45 ml/kg−1 body weight KME or Placebo 30-min prior to completing a 75 g OGTT. β-OHB and BDNF were measured via blood samples at fasting baseline (pre-OGTT) and 120 min post-OGTT. Results: Study 1: KME significantly increased β-OHB by 800 ± 454% (p < 0.001). BDNF significantly decreased post-OGTT compared to pre-OGTT in Placebo (718.6 ± 830.8 pg/ml vs. 389.3 ± 595.8 pg/ml; p = 0.018), whereas BDNF was unchanged in KME (560.2 ± 689.6 pg/ml vs. 469.2 ± 791.8 pg/ml; p = 0.28). Study 2: KME significantly increased β-OHB by 1,586 ± 602% (p < 0.001). BDNF was significantly higher post-OGTT in the KME condition in OB (time × condition interaction; p = 0.037). There was a moderate relationship between β-OHB and ∆ %BDNF (r = 0.616; p < 0.001). Fasting plasma BDNF was significantly lower in OB compared to NW (132.8 ± 142.8 pg/ml vs. 639.4 ± 756.8 pg/ml; g = 0.845; p = 0.002). Conclusions: Plasma BDNF appears differentially impacted by KME ingestion with OGTT in OB compared to NW. Raising β-OHB via KME may be a strategy for increasing/protecting BDNF during hyperglycemia.